Mortality and Pulmonary Embolism in Acute Respiratory Distress Syndrome From COVID-19 vs. Non-COVID-19 - Kutsogiannis, Demetrios J.; Alharthy, Abdulrahman; Balhamar, Abdullah; Faqihi, Fahad; Papanikolaou, John; Alqahtani, Saleh A.; Memish, Ziad A.; Brindley, Peter G.; Brochard, Laurent; Karakitsos, Dimitrios (Frontiers in Medicine, 2022)
Abstract Purpose There may be a difference in respiratory mechanics, inflammatory markers, and pulmonary emboli in COVID-19 associated ARDS versus ARDS from other etiologies. Our purpose was to determine differences in respiratory mechanics, inflammatory markers, and incidence of pulmonary embolism in patients with and without COVID-19 associated ARDS admitted in the same period and treated with a similar ventilation strategy. Methods A cohort study of COVID-19 associated ARDS and non COVID-19 patients in a Saudi Arabian center between June 1 and 15, 2020. We measured respiratory mechanics (ventilatory ratio (VR), recruitability index (RI), markers of inflammation, and computed tomography pulmonary angiograms. Results Forty-two patients with COVID-19 and 43 non-COVID patients with ARDS comprised the cohort. The incidence of “recruitable” patients using the recruitment/inflation ratio was slightly lower in COVID-19 patients (62% versus 86%; p = 0.01). Fifteen COVID-19 ARDS patients (35.7%) developed a pulmonary embolism as compared to 4 (9.3%) in other ARDS patients (p = 0.003). In COVID-19 patients, a D-Dimer ≥ 5.0 mcg/ml had a 73% (95% CI 45-92%) sensitivity and 89% (95% CI 71-98%) specificity for predicting pulmonary embolism. Crude 60-day mortality was higher in COVID-19 patients (35% versus 15%; p = 0.039) but three multivariate analysis showed that independent predictors of 60-day mortality included the ventilatory ratio (OR 3.67, 95% CI 1.61 to 8.35), PaO2/FIO2 ratio (OR 0.93; 95% CI 0.87 to 0.99), IL-6 (OR 1.02, 95% CI 1.00-1.03), and D-dimers (OR 7.26, 95% CI 1.11-47.30) but not COVID-19 infection. Conclusion COVID-19 patients were slightly less recruitable and had a higher incidence of pulmonary embolism than those with ARDS from other etiologies. A high D-dimer was predictive of pulmonary embolism in COVID-19 patients. COVID-19 infection was not an independent predictor of 60-day mortality in the presence of ARDS.